Réponses

Meilleure réponse !
2014-09-12T13:39:12+02:00
A = (9)+(7) = 16

B = (8)+(-13) = -5

C = (-15) + (-6) = -21

D = (12) + (-12) = 0

E = (-9) + (-9) = -18

F = (-4) + (11) = 7
  • Utilisateur Brainly
2014-09-12T14:17:28+02:00
A= (+ 9) - (+ 7)
A= - 7 + 9
A= 2

B= (+ 8) - (- 13)
B= 8 + 13
B= 21

C=(- 15) - (- 6)
C= - 15 + 6
C= - 9

D= (+ 12) - (- 12)
D= 12 + 12
D= 24

E= (- 9) - (- 9)
E= - 9 + 9
E= 0

F= - 4 - (+ 11)
F= - 4 + (- 11)
F= - 15
A= (+ 9) - (+ 7)
A= - 7 + 9
A= 2

B= (+ 8) - (- 13)
B= 8 + 13
B= 21

C=(- 15) - (- 6)
C= - 15 + 6
C= - 9

D= (+ 12) - (- 12)
D= 12 + 12
D= 24

E= (- 9) - (- 9)
E= - 9 + 9
E= 0

F= - 4 - (+ 11)
F= - 4 + (- 11)
F= - 15